Access to civics content and evidence-based instructional approaches in U.S. schools - Corey Savage; Saki Ikoma (Large-scale Assessments in Education)
Abstract Background Civic learning is an increasingly salient topic in research, policy, and practice. However, the recent empirical evidence on access to civic learning opportunities in the U.S. is limited, and monitoring learning opportunities is equally as important as monitoring learning outcomes. Methods We build on prior research using survey items from the 2018 National Assessment of Educational Progress (NAEP) Civics Assessment and provide descriptive evidence on disparities in access to three categories of civics content and four evidence-based instructional approaches. We describe inequalities in opportunities by student characteristics, school characteristics, and state characteristics among a national sample of more than 10,000 Grade 8 students. Results Our findings diverge from most of the prior evidence regarding disparities in access by race, ethnicity, or socioeconomic background, favoring Black students, Hispanic students, and students of relatively lower socioeconomic backgrounds. English learners and students with disabilities also reported greater exposure to civic learning opportunities than their counterparts. Other findings include inequalities across school type/sector, school location, and state testing policy. Conclusions These novel findings raise new questions about the distribution of civic learning opportunities in U.S. schools. We discuss implications and the need for further research on this important topic with data that allows for continued improvements with internal and external validity.